AGRICULTURE AND LAW - Mahipal, Naresh; Garg, Jyoti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This chapter delves into the complex relationship between agriculture and law in the Indian context. It explores the legal framework governing agriculture, highlighting the significant legislations, policies, and regulations that have shaped India's agricultural sector. The chapter also discusses the impact of these laws on farmers' rights, land ownership, agricultural practices, and the environment. Through an examination of historical developments and current challenges, the chapter offers insights into the potential avenues for future reforms in agriculture and law.